Multi-Criteria Decision-Making Techniques for Optimal In-House Storage Location Selection - Průša, Petr; Mikušová, Nikoleta; Becková, Helena (MDPI, 2024)
Storage is a key task of a logistics enterprise. Effective storage processes can increase the efficiency of enterprise logistics processes and positively affect logistics costs. Therefore, it is very important to deal with selecting storage locations within the enterprise area. The present paper deals with the optimal in-house storage location. The research was realized through a Czech Republic brewing company case study which aimed to find and select the best in-house storage location. The decision-making methods chosen for this solution were the additive ratio assessment method and the combined compromised solution method. While these methods are rarely used for this kind of solution-making, they helped to find the best location for reasonable storage in the research enterprise.
Techniky vícekriteriálního rozhodování pro výběr optimálního umístění vnitropodnikového skladu
Keywords: logistics; location; decision making; storage; warehouses; logistika; umístění; rozhodování; skladování; sklady